The Influence of Games and Intelligences to Ability in Mathematics for TK-Bâs Children - Huliyah, Muhiyatul (Indonesian Journal of Islamic Early Childhood Education, 2017)
This article reported the result of research for the influence of games and intelligences to ability in mathematics for TK-Bâs children. The research was held in TK/RA Daarul Muqimien of Buaranjati village, Sukadiri subdistrict, Tangerang regency. The amount of sample are 40 TK-Bâs children. The method used was experimental with 2x2 factorial design. The results of this research are : (1) there was non significant difference to ability in mathematics for TK-Bâs children who given by Monopoly game and TK-Bâs children who given by Snakes-Ladders game; (2) there was non significant difference to ability in mathematics for TK-Bâs children with high intelligence who given by monopoly game and Snakes-Ladders game; (3) ability in mathematics for TK-Bâs children with low intelligence who given by Monopoly game lower than children who given by Snakes-Ladders game; (4) there was significant influence of interaction between games and intelligence to ability in mathematics for TK-Bâs children. Both monopoly game and Snakes-Ladders game could improve the ability in mathematics for TK-Bâs children.